Intervention on the phenomenon of bullying in elementary school - Danial, Muhammad; Akbar, Tian Khusni (Journal of Indonesian Progressive Education, 2025)
This research aims to investigate the effectiveness of interventions addressing the phenomenon of bullying in elementary schools. Bullying is a significant issue with detrimental effects on the psychological and social well-being of students. Appropriate interventions are expected to mitigate or even eliminate bullying behaviors within the elementary school environment.The study uses descriptive qualitative research, where the subjects used to lead the data are principals, teachers and students in grades 1 to 6. Data collection is done through observation, interviews and documentation. Furthermore, the data is analyzed and described in the form of a narrative so as to produce a conclusion. The conclusion of the results of the study is that SDN X P classifies three bullyings that occur in schools, namely physical, relational and verbal bullying. The preventive and repressive steps taken by SDN X P are by providing support to victims, making regulations regarding bullying, providing examples, one of which is PAI lessons, detecting bullying acts earlier and providing solutions related to bullying.